2016
DOI: 10.1590/s0102-865020160080000010
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in carotid arteries of patients submitted to carotid endarterectomy. The role of aging process

Abstract: PURPOSE:To evaluated the role of oxidative stress on aging process in patients submitted to carotid endarterectomy. METHODS:Twenty patients were divided into two groups: older group (≥ 70 years old); and the younger group (< 70 years old).We evaluated the reactive oxygen species (ROS) concentration, nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase, superoxide dismutase (SOD) and catalase (CAT) activities as so as nitrite levels in fragments of carotid arteries harvested during carotid endarterectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Accumulating ROS, important regulators in aging progression, have been reported in aged arteries. In human carotid specimens, higher ROS levels were found in the older age group (>70 years old) [10]. Similarly, results obtained from rodent studies also showed that arterial oxidative stress was significantly higher in aged groups [1113].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Accumulating ROS, important regulators in aging progression, have been reported in aged arteries. In human carotid specimens, higher ROS levels were found in the older age group (>70 years old) [10]. Similarly, results obtained from rodent studies also showed that arterial oxidative stress was significantly higher in aged groups [1113].…”
Section: Discussionmentioning
confidence: 95%
“…Accumulating ROS in aged arteries may contribute to mitochondrial dysfunction as well as imbalances in expressions or activities of oxidant/antioxidant enzymes, e.g., NADPH oxidase, nitric oxide synthase (NOS), superoxide dismutase (SOD), and catalase (CAT). For example, NADPH oxidase activity was upregulated in carotid arteries of older patients (>70 years old), but no significant difference in SOD or CAT activities was detected between older and younger groups [10]. Moreover, upregulation of endothelial NOS expression and activity, accumulation of superoxide and protein nitrotyrosination, as well as a reduction in SOD activity were also obviously observed in the aortas of aged rodents [1113].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no certain medical treatment procedure developed for CAS today, the use of some therapeutic drugs such as statins, antiplatelet drugs, antihypertensive in combination with a healthy lifestyle will lead to the positive progress of the disease [15]. Oxidative stress has a significant role in endothelial dysfunction so in CAS pathogenesis [21][22][23][24][25]. Many researches state that high fructose intake induces oxidative stress by causing a decrease in the level of endogenous antioxidants and free radical production [12].…”
Section: Discussionmentioning
confidence: 99%
“…e immersion of the field of senescence has also added valuable knowledge towards a deeper understanding of the pathogenic mechanisms [146][147][148][149]. Deciphering "vascular senescence" has led to the identification of intracellular targets for the development of novel therapies and new prevention and diagnostic strategies [150][151][152][153][154].…”
Section: Discussionmentioning
confidence: 99%